Inheritance [large type] - Roberts, Nora (Roberts, Nora. Lost bride trilogy, 2023)
"Sonya MacTavish is stunned to learn that her late father had a twin he never knew about--and that her newly discovered uncle has left almost everything he owned, including Victorian house, which the will stipulates she must live in for at least three years. She sees a painting by her father inexplicably hanging in her deceased uncle's office, and a portrait of a woman named Astrid, who the lawyer, refers to as the first "lost bride." It's becoming clear that Sonya has inherited far more than a house. She has inherited a centuries-old curse, and a puzzle she must solve if there is any hope of breaking it"--